Abiotic transformation of polycyclic aromatic hydrocarbons via interaction with soil components: A systematic review. Issue 5 (4th March 2023) - Liu, Jinbo; Zhang, Chi; Jia, Hanzhong; Lichtfouse, Eric; Sharma, Virender K.
Abstract: Natural attenuation is a major ecosystem function allowing to abate soil organic contaminants such as polycyclic aromatic hydrocarbons (PAHs). Biodegradation of PAHs is classically considered as the major driver of natural attenuation, yet the role of abiotic transformation, including photodegradation, chemical oxidation, formation of non-extractable residues, and polymerization, has been overlooked due to the lack of investigations until recently. This paper reviews PAHs dissipation in soils by abiotic processes such as photodegradation and oxidation catalyzed by inorganic minerals and organic matters. The role of soil components on degradation rates, pathways, and mechanisms are discussed. The products of PAHs abiotic transformation and their potential risks are also described. Abiotic transformations are mainly controlled by interactions between PAHs and clay minerals, metal oxides/hydroxides, and soil organic matter. PAH photodegradation proceeds by both direct and indirect photolysis processes, which are enhanced in the presence of natural photosensitizers, for example, organic matter, and photocatalysts, for example, metal oxides/hydroxides. PAHs can also be chemically/catalytically oxidized by metal oxides/hydroxides, for example, MnO2, Fex Oy, and clay minerals without light irradiation. Overall, PAHs transformation depends on their electron-donating properties, mineral electron-accepting properties, pH, temperature, moisture, and oxygen content. Following the elucidation of the transformative mechanism, knowledge to understand the impact of abiotic transformation on biodegradation are delineated. Future investigations are needed to advance the correlation of laboratory generated rates to the field applications, and the potential applications of natural attenuation based on abiotic processes are proposed. Abstract : UF0001